2013
DOI: 10.1208/s12248-013-9495-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Protein Drug–Drug Interactions: Navigating the Knowledge Gaps–Highlights from the 2012 AAPS NBC Roundtable and IQ Consortium/FDA Workshop

Abstract: Abstract. The investigation of therapeutic protein drug-drug interactions has proven to be challenging. In May 2012, a roundtable was held at the American Association of Pharmaceutical Scientists National Biotechnology Conference to discuss the challenges of preclinical assessment and in vitro to in vivo extrapolation of these interactions. Several weeks later, a 2-day workshop co-sponsored by the U.S. Food and Drug Administration and the International Consortium for Innovation and Quality in Pharmaceutical De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
(40 reference statements)
0
43
0
1
Order By: Relevance
“…However, some studies have shown an increase in cytokine expression following mAb administration; many cytokines in turn are known to modify CYP and transporter activity, with consequential implications for the clearance of small molecules. [79][80][81] The FDA 2012 draft guidance on DDIs and expert review of this guidance have produced a strategy to assess DDIs with therapeutic proteins. 81,82 A risk assessment for the therapeutic protein is necessary, including its potential to modulate inflammatory or other cytokines, any likely small-molecule comedications, clearance mechanism for all agents that may be coadministered (including the therapeutic protein), and potential for CYP-mediated interaction between the protein and comedications.…”
Section: Drug-drug Interaction Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown an increase in cytokine expression following mAb administration; many cytokines in turn are known to modify CYP and transporter activity, with consequential implications for the clearance of small molecules. [79][80][81] The FDA 2012 draft guidance on DDIs and expert review of this guidance have produced a strategy to assess DDIs with therapeutic proteins. 81,82 A risk assessment for the therapeutic protein is necessary, including its potential to modulate inflammatory or other cytokines, any likely small-molecule comedications, clearance mechanism for all agents that may be coadministered (including the therapeutic protein), and potential for CYP-mediated interaction between the protein and comedications.…”
Section: Drug-drug Interaction Potentialmentioning
confidence: 99%
“…[79][80][81] The FDA 2012 draft guidance on DDIs and expert review of this guidance have produced a strategy to assess DDIs with therapeutic proteins. 81,82 A risk assessment for the therapeutic protein is necessary, including its potential to modulate inflammatory or other cytokines, any likely small-molecule comedications, clearance mechanism for all agents that may be coadministered (including the therapeutic protein), and potential for CYP-mediated interaction between the protein and comedications. Options for clinical assessment of DDIs include a population PK approach using data from multiple phase 3 studies, which should suffice to recommend dosing adjustments when the signal of interaction is clear and large.…”
Section: Drug-drug Interaction Potentialmentioning
confidence: 99%
“…BiTE® antibody constructs are unlikely to be victims of DDI as they do not undergo CYP‐mediated clearance, although they may perpetrate DDI indirectly. Although BiTE® antibody constructs do not directly affect CYP enzyme activities, transient cytokine elevation, especially of IL‐6, has been observed in clinical trials with blinatumomab and in preclinical studies with blinatumomab and other BiTE® antibody constructs, and the suppression of CYP enzymes in response to cytokine elevation has been well documented 79. A dedicated DDI study in this population would be impractical, however, so a physiologically based pharmacokinetic (PBPK) model was developed to evaluate the impact of IL‐6 elevation on CYP suppression after blinatumomab administration 80.…”
Section: Clinical Pharmacology Of Blinatumomabmentioning
confidence: 99%
“…Cultured hepatocytes are useful for mechanistic studies related to the impact of a cytokine on gene expression and activity, but there are inherent limitations Kenny et al, 2013): 1) hepatocytes do not reflect the complex interactions between multiple cytokines and cell types that play a role in vivo in inflammatory diseases; 2) high levels of interlaboratory and interdonor variability in cultured hepatocytes make quantitative interpretation of results challenging; and 3) hepatocyte monocultures are relevant only for studying cytokines with receptors directly expressed on hepatocytes. Based on these limitations, applying in vitro data to predict cytokine-mediated DDIs associated with anti-inflammatory TPs is challenging and currently not recommended .…”
Section: Introductionmentioning
confidence: 99%